Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858445
|View full text |Cite
|
Sign up to set email alerts
|

The Quantified Patient in the Doctor's Office

Abstract: While the Quantified Self and personal informatics fields have focused on the individual's use of self-logged data about themselves, the same kinds of data could, in theory, be used to improve diagnosis and care planning. In this paper, we seek to understand both the opportunities and bottlenecks in the use of self-logged data for differential diagnosis and care planning during patient visits to both primary and secondary care. We first conducted a literature review to identify potential factors influencing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…In contrast, past literature contends that physicians perceive the data from these devices to be unreliable [36]. However, Nundy et al found that overall this data is more trustworthy than self-report, which providers perceive that some patients misrepresent their activity to please the providers [26].…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, past literature contends that physicians perceive the data from these devices to be unreliable [36]. However, Nundy et al found that overall this data is more trustworthy than self-report, which providers perceive that some patients misrepresent their activity to please the providers [26].…”
Section: Discussionmentioning
confidence: 95%
“…The arrival of mHealth technologies (including wearables, self-tracking software and health apps) and the subsequent explosion in the amount of data related to health, have enabled the logic of empowerment to gain more widespread and intense support than ever before (Lupton 2013). (West et al 2016), and most recently the NHS Long Term Plan (2019), 6 have come to rely on the unquestioned belief that people who have unlimited access to their personal health data (van Roessel et al 2017;Swan 2009) will take on the role of what Swan (2012) terms the 'empowered biocitizen.' These empowered individuals are framed as being able to acknowledge that they have both the responsibility (Wardrope 2015) for managing their own health, and the tools for doing so 7 (Swan 2012).…”
Section: The Roots Of the Empowerment Narrativementioning
confidence: 99%
“…Chung et al suggest that tracking tools be designed to more flexibly support collaboration and provide better visualizations [8], while West et al suggest that tracking tools make it easier for clinicians to reason about the data they collect [55]. Schroeder et al suggest that tools support exploration through flexibility and simplicity, and emphasize the generation of actionable insights [48].…”
Section: Related Workmentioning
confidence: 99%